Re-Building Communities: Voluntary Resettlement From Protected Areas in India - Karanth, Krithi K.; Kudalkar, Sahila; Jain, Shivangi (Frontiers in Ecology and Evolution, 2018)
Exclusion of people from wilderness to minimize anthropogenic threats to wildlife forms the historical basis for the establishment of some protected areas. Conservation efforts to resettle people from protected areas remain controversial as they often fail to address people’s expectations and rebuild lives, especially in Africa and South Asia. Resettlement projects are especially challenging for the Indian government, with an estimated 4.3 million people sharing spaces with megafauna such as tigers and elephants within protected areas. Current Indian government policies focus on cash-based or a combined cash-land compensation package for families voluntarily relocating. We surveyed 592 households from four Indian protected areas and evaluated people’s decisions to move relative to government policy provisions. Many (89%) households wanted to move for better education, healthcare, roads, agriculture, less human-wildlife conflict, and the government-aid package. Wage-labor dependent households chose to move due to high human-wildlife conflict, poorer small landholders for better agricultural opportunities, and larger households to avail government package benefits. Current government policies place heavy emphasis on agriculture-based livelihoods, poorly support other developmental needs or provide for alternative livelihoods. We call for greater transparency and participation of beneficiaries in the process, policy expansion to diversify skills and vocational training, accompanied by independent long-term monitoring post-resettlement.